Intercropping impacts growth in the forage cactus, but complementarity affords greater productivity, competitive ability, biological efficiency and economic return - Salvador, Kaique Renan da Silva; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Alves, Cleber Pereira; Araújo Júnior, George do Nascimento; Silva, Marcelo José da; Souza, Leonardo Francelino de; Queiroz, Mário Adriano Ávila; Campos, Fleming Sena; Gois, Glayciane Costa; França, José Geraldo Eugênio de; Nunes Filho, José; Steidle Neto, Antonio José; et al. (Elsevier, 2024)
CONTEXT: Soil and climatic conditions limit forage production in semi-arid environments. Planting crops adapted to these elements, combined with management practices such as intercropping and irrigation, can ensure the sustainability of animal feed. OBJECTIVE: The aim of this study was to evaluate growth, forage productivity, soil water balance, water indices and the indices of biological efficiency, competitive ability, and economic return in a dense crop of forage cactus, grasses, and legumes under single and intercropping systems in a semi-arid environment. METHODS: The study was carried out from 2020 to 2022 in Serra Talhada, Pernambuco, Brazil. The plants used were the ‘Orelha de Elefante Mexicana’ (OEM) clone of the forage cactus, pigeon pea (‘crioula’), millet (‘Bulk-01’) and sorghum (‘SF15’). A randomised block design was adopted, with three repetitions, including single crops of the forage cactus, sorghum, millet and pigeon pea, as well as the cactus intercropped with pigeon pea, millet and sorghum. Biometrics and biomass were checked to determine morpho-physiological indices, phenology, cutting time, biological efficiency and competitive ability. The soil moisture was also monitored, and the soil water balance quantified. The water indices and economic return were then calculated. RESULTS AND CONCLUSIONS: Growth rates and phenology were not affected by intercropping, only by the cutting time. During the first season, the single sorghum and cactus-pigeon pea system showed a variation in soil water storage of 26 mm, while during the second season, the single cactus stored 66.74 mm. The actual evapotranspiration ranged from 1109 in the cactus-millet system to 1152 mm in the single cactus and millet (1st season), and from 1510 in the single cactus to 1570 mm in the sorghum (2nd season). The cactus-sorghum system was the most productive, with 460.53 Mg FM ha−1 and 43.55 Mg DM ha−1 in season one, while in season two, the single cactus obtained 237.64 Mg FM ha−1 and 26.71 Mg DM ha−1. Intercropping promotes more productive stability and feed diversity, as well as greater biological efficiency, competitive ability and economic return. SIGNIFICANCE: Understanding the changes that exist in a intercropping system is important, especially in semi-arid regions, since these have distinct characteristics that impact the development of crops. Thus, this work contributes comprehensively to resilient practices for the semi-arid, seeking to ensure the sustainability of the intercropping systems and understand the interrelationship between species from the management adopted.
Keywords: Intercropping system; Morpho-physiological indices; Phenology